2014
DOI: 10.1002/ange.201403905
|View full text |Cite
|
Sign up to set email alerts
|

NMR Signatures of the Active Sites in Sn‐β Zeolite

Abstract: Dynamic nuclear polarization surface enhanced NMR (DNP-SENS), Mçssbauer spectroscopy, and computational chemistry were combined to obtain structural information on the active-site speciation in Sn-b zeolite. This approach unambiguously shows the presence of framework Sn IV -active sites in an octahedral environment, which probably correspond to so-called open and closed sites, respectively (namely, tin bound to three or four siloxy groups of the zeolite framework).Heterogeneous catalysts with well-defined isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 52 publications
5
44
1
Order By: Relevance
“…This result indicates that the Zn-Sn-Beta zeolite does not appear to have extra-framework ZnO and SnO 2 which is consistent to the XRD data. In addition, Hermans et al confirmed that the presence of framework Sn in the Sn-Beta zeolite prepared by SSIE using dynamic nuclear polarization surface enhanced nuclear magnetic resonance24.…”
Section: Resultsmentioning
confidence: 93%
“…This result indicates that the Zn-Sn-Beta zeolite does not appear to have extra-framework ZnO and SnO 2 which is consistent to the XRD data. In addition, Hermans et al confirmed that the presence of framework Sn in the Sn-Beta zeolite prepared by SSIE using dynamic nuclear polarization surface enhanced nuclear magnetic resonance24.…”
Section: Resultsmentioning
confidence: 93%
“…The advent of Dynamic Nuclear Polarization (DNP), using gyrotron microwave (MW) sources, combined with MAS has opened the door to many advanced studies of solids at high magnetic fields [1]. The development and implementation of high field gyrotrons up to the Terahertz range has enabled the construction of high field MAS-DNP instruments, and led to the commercialization of MAS-DNP spectrometers by Bruker Inc. [2] operating up to 18 T. Theses high field DNP instrument developments have triggered a vast interest of the solid-state NMR community in MAS-DNP experiments, both for biological [3][4][5][6][7][8][9][10][11] and material science [12][13][14][15][16][17][18][19][20][21][22] applications. Most of these experiments performed today are using nitroxide based bi-radicals such as TOTAPOL [23,24,2,8,25,26,9], and recently new nitroxide based biradicals have been introduced with varying longitudinal relaxation times, phase memory times (or transverse relaxation time), electron-electron dipolar couplings, and relative gÀtensor orientations such as AMUPOL, bCTbK, or TEKPOL [27,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the isomerization of glucose to fructose with Sn-Beta, various authors have attributed the observed decrease in turnover frequency with increasing metal loading to the resence of framework Sn sites with different activities or the formation of condensed SnO x species. 31,32 …”
Section: Introductionmentioning
confidence: 99%
“…However, many of these methods are difficult to implement reliably or routinely. 6 For instance, diffuse reflectance ultraviolet spectroscopy (DRUV), 30,31,33 X-ray diffraction, 30,34 119 Sn Mössbauer spectroscopy, 31 X-ray photoelectron spectroscopy (XPS), 33 and Raman spectroscopy 31,33 provide only qualitative or semi-quantitative measurements. Synchrotron-based techniques are powerful but difficult to implement on a routine basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation